Intrathoracic manifestation in Rosai Dorfman Disease (RDD): A case report with review of the literature (Indian Journal of Case Reports, 2019)
Rosai-Dorfman disease, previously known as sinus histiocytosis with massive lymphadenopathy (SHML) is one of the rare benign idiopathic proliferative diseases of phagocytic histiocytes. Majority of the patients present with painless massive cervical lymphadenopathy but intrathoracic involvement is rarely reported. Here, we report the case of a 57-year-old male with a history of chest pain, shortness of breath and generalized weakness of two-month duration. The diagnosis was formed by core biopsy of the axillary lymph node with typical emperipolesis and Immunohistochemistry markers